Relationship between Nutritional Status and Toddler Psychomotor Development at the Marbau Health Center in North Labuhanbatu Regency in 2022 - Mayasari, Mayasari (Paspama Institute, 2023)
Psychomotor development in children under three years can be monitored by looking at gross and fine motor skills. One of the important factors that influence the psychomotor development of children under three years is the nutritional factor. This study aims to determine the relationship between nutritional status and toddler psychomotor development at the Marbau Health Center, Labuhanbatu Utara District in 2022. This research is a cross-sectional descriptive correlation approach. The research was conducted from 20 September 2022 to 30 September 2022. The population was 158 people. Sampling using accidental sampling with a total sample of 47 people. Data processing is done by editing, coding, tabulation, entry and data processing. The test that was carried out was the chi-square test. The results of the study showed that the majority of toddlers' nutritional status at the Marbau Health Center in North Labuhanbatu Regency were well nourished and the majority of toddlers' psychomotor development was appropriate. Based on the results of the chi-square test, the value of p = 0.001 <a = 0.05 was obtained. So it can be concluded that there is a relationship between nutritional status and toddler psychomotor development at the Marbau Health Center in Labuhanbatu Utara Regency in 2022. The suggestion in this study is that the Marbau Health Center should continue to pay attention to the suitability of toddlers' nutritional status and psychomotor development in order to create a healthy and smart generation going forward.